Substance Use Disorders and risk of suicide attempts: The role of genes and environment in a Swedish Population-Based Cohort - Alexis Edwards; Séverine Lannoy; Mallory Stephenson (OSF Registries, 2022)
Background: Previous studies have demonstrated substantial associations between Substance Use Disorders (SUD) and suicidal behavior (Edwards et al., 2020; Lynch et al., 2020), while others supported shared genetic liability and the influence of common environmental factors (Bridge et al., 1997; Edwards et al., 2018).
Purpose: In this study, we seek to better understand the risk of suicide attempts in a sample of individuals with registrations for SUD, including alcohol use disorder and drug use disorders. We will focus on both familial-genetic and environmental predictors. In particular, we are interested in exploring how environmental factors (distal factors, such as childhood stressors, and proximal factors such as socioeconomic status) may moderate the genetic risk for suicide attempts among individuals with SUD.
Methods: We will identify a sample of individuals with SUD using nationwide Swedish medical, pharmacy, and criminal registries and evaluate the role of genetic (family genetic risk scores) and environmental (childhood stressors, parental, marital, and socioeconomic status) factors. The relative risk of suicide attempt among SUD individuals will be assessed using Cox regression models. Then, to account for familial factors and improve causal inference, we will compare groups of cousin and full sibling pairs who are concordant for SUD and discordant in their exposure to putative risk factors (co-relative analyses; Kendler et al., 2014).

The co-relative method is an extension of the co-twin control design (Kendler, 1993) used to improve causal inference. Basically, if the association between a putative risk factor (e.g., socioeconomic status) and outcome (suicide attempt) is entirely causal, then the risk of suicide attempt in those having a low socio-economic status would be similar in the population and across relative pairs of increasing genetic correlation (cousins and full siblings). If the association is attributable in part to familial factors (including genetic and familial environmental factors), accounting for those shared factors will result in less pronounced associations.
Keywords: Mental Disorders; Psychiatry and Psychology; Public Health; Medicine and Health Sciences